Ancient history from coins - Howgego, C. J. (Approaching the ancient world., 1995)
Ancient History from Coins demystifies numismatics, introducing students to the techniques, methods, problems and advantages of using coins to do ancient history, and provides - through numerous examples - a history of coinage.